CHARACTERISTICS OF PERMEABEL GEOLOGICAL STRUCTURE BASED ON AUTOMATIC LINEAMENT EXTRACTION USING MODIFIED SEGMENT TRACING ALGORTIHM ON ALOS PALSAR AND FIELD STUDY AT DARAJAT GEOTHERMAL FIELD - Kurniawahidayati, Beta
Geological structure plays important role in geothermal system. Not only as subsurface permeability source but also as system boundary. In early exploration stage, geological structure identification generally done by delineating lineaments from sattelite imagery manually. Technology advancement allows automatic lineament extraction by using Modified Segment Tracing Algorithm (mSTA) from ALOS PALSAR imagery. This method able to produce lineaments more objective and faster, but cannot differentiate lineament from geological structure with lineament caused by other geological control such as lithological contact or man made feature. Therefore, a guidance is needed to detect permeable geological structure that can be detected from ALOS PALSAR imagery. Method used in this research is doing automatic lineament extraction with mSTA in ALOS PALSAR imagery, produced interpretative geological structure map from lineament and followed by validation of structural geology with field study, analized geological structure characteristic towards automatic lineament extraction from mSTA. Field study and mSTA linemaent analysis shows structural geology can be detetcted with delineation of continuous and overlayed line in lineament map, and lineament density observation from mSTA extraction. Guidance obtained from this research are permeable faults will be characterized by the existence of extensional and transitional structures, frequency and lenght linemanet density contrast, presence of pull apart basin in strike-slip fault, and appearance of surface manifestations characterized by medium to high frequency and lenght lineament density. The conclusion of this study is correlation between interpretive geological structures from lineament and density maps towards valid geological structures is quite good with 85% match percentage. The characteristics and guidance that have been generated have been validated by applied it to confirmed structural geology in study area Kendang Fault.